(NaNAIT bAQNDUR (B:s (NsTATXI(B, (NINTERWX@(B, (N\SSE(B: [(No PRAWOZA]ITNICE(B, (NPEREWOD^ICE(B, (NOB]ESTWENNOJ DEQTELXNICE(B] /s - (NtOROSQN(B, (N{U[ANs; (NbAQNDUR(B, (NaREGs ((NeREWAN (B:s (NzANGAK(B,s, 2013)
(Nw SBORNIK WKL@^ENY IZBRANNYE \SSE(B, (NINTERWX@(B, (NSTATXI(B, (NPEREWODY aNAIT bAQNDUR(B, (NWOSPOMINANIQ I OTZYWY O NEJ DRUZEJ I KOLLEG(B.s
Keywords: d; (NpRAWOZA]ITNIKIs; (NpEREWODYs; (NoB]ESTWENNAQ DEQTELXNOSTXs; (NpUBLICISTIKAs; (NaRMQNSKIE OB]ESTWENNYE DEQTELIs